Development of a health promotion program for patients with Uncontrolled Type 2 Diabetes at Phurua hospital - boonsriphoom, Supaphorn (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2026)
Diabetes mellitus is a major public health problem with a rapidly increasing prevalence worldwide and in Thailand. At Phurua Hospital, many patients with type 2 diabetes are unable to achieve optimal glycemic control, defined as glycated hemoglobin (HbA1c) levels ≥7%, which increases the risk of long-term complications. This quasi-experimental study aimed to develop and evaluate the effectiveness of a health promotion program for patients with uncontrolled type 2 diabetes at Phurua Hospital, Thailand. A one-group pretest–posttest design was employed. The sample consisted of 280 patients with HbA1c ≥7%, recruited through consecutive sampling between October 2023 and June 2024. The program was developed based on Pender’s Health Promotion Model and included multidisciplinary education, skill training, and continuous follow-up. Data were collected using a diabetes knowledge questionnaire, a self-management skills assessment, and laboratory HbA1c measurements. Descriptive statistics and paired sample t-tests were used for analysis. Results showed that diabetes knowledge significantly increased from 12.79 (SD = 2.66) to 17.97 (SD = 0.86) (mean difference = 5.18, t = 31.88, p < 0.001). Self-management skills significantly improved across all domains (p < 0.001). Mean HbA1c significantly decreased from 8.72% (SD = 1.77) to 8.21% (SD = 1.66) (mean difference = −0.51, t = −5.95, p < 0.001). The health promotion program effectively improved diabetes knowledge, self-management skills, and glycemic control among patients with uncontrolled type 2 diabetes. The program shows potential as a practical and sustainable model for diabetes care in community hospitals and primary healthcare settings.